Viral UL8 Is Involved in the Antiviral Activity of Oleanolic Acid Against HSV-1 Infection - Shan, Tianhao; Ye, Ju; Jia, Jiaoyan; Wang, Zhaoyang; Jiang, Yuzhou; Wang, Yiliang; Wang, Yifei; Zheng, Kai; Ren, Zhe (Frontiers in Microbiology, 2021)
Herpes simplex virus type 1 (HSV-1) is highly prevalent in humans and can cause severe diseases, especially in immunocompromised adults and newborns, such as keratitis and herpes simplex encephalitis. At present, the clinical therapeutic drug against HSV-1 infection is acyclovir (ACV), and its extensive usage has led to the emergence of ACV-resistant strains. Therefore, it is urgent to explore novel therapeutic targets and anti-HSV-1 drugs. This study demonstrated that Oleanolic acid, a pentacyclic triterpenoid widely existing in natural product, had strong antiviral activity against both ACV-sensitive and -resistant HSV-1 strains in different cells. Mechanism studies showed that Oleanolic acid exerted its anti-HSV-1 activity in the immediate early stage of infection, which involved the dysregulation of viral UL8, a component of viral helicase-primase complex critical for viral replication. In addition, Oleanolic acid significantly ameliorated the skin lesions in an HSV-1 infection mediated zosteriform model. Together, our study suggested that Oleanolic acid could be a potential candidate for clinical therapy of HSV-1 infection-related diseases.